Penurunan Keluhan Menopause dengan Latihan Kekuatan otot, Tulang dan Sendi (OTTUSEN) - Dame Evalina Simangunsong; Tengku Sri Wahyuni (Jurnal Kesehatan Manarang, 2020)
The journey of life in the age of 40 – 55 year experience in crisis is a woman's life, which will be old and experiencing menopause. Various complaints will be experienced by women during the menopause symptoms ranging from mild to severe. This complaint is called with complaints or climacterik syndrome. Prevention efforts with health education in avoiding risky behavior in menopausal women need to be emphasized. Doing physical exercise every day can be an alternative in addressing the various symptoms experienced at the time of menopause. Maintain body fitness while maintaining the balance of weight and physical activity in the form of strength training muscles, bones and joints need to be applied in reducing menopausal complaints. The purpose of this research was to analyze the influence of strength training muscles, bones and joints against a decrease in complaints of menopause. This type of research, quasi experiments (draft two group pretest-posttest design with control group), involves the menopausal women, as many as 70 people. The data is processed with the univariate analysis, T-test with bivariate. There is a difference in the average score decline in menopausal complaints on measuring pretest and posttest on intervention group significantly. there's a difference, decreased menopausal complaints before and after the application of exercise muscle strength and bone. Movement of age-appropriate physical activity with a frequency three times a week and the duration of 30 minutes each exercise needs to be done and ongoing.